Cholesterol induced autophagy via IRE1/JNK pathway promotes autophagic cell death in heart tissue - SÖZEN, AHMET ERDİ; KARTAL ÖZER, NESRİN (W B SAUNDERS CO-ELSEVIER INC, 2020)
Background: Cardiovascular diseases (CVDs), with highest mortality and morbidity rates, are the major cause of death in the world. Due to the limited information on heart tissue changes, mediated by hypercholesterolemia, we planned to investigate molecular mechanisms of endoplasmic reticulum (ER) stress and related cell death in high cholesterol fed rabbit model and possible beneficial effects of alpha-tocopherol. Methods: Molecular changes in rabbit heart tissue and cultured cardiomyocytes (H9c2 cells) were measured by western blotting, qRT-PCR, immunflouresence and flow cytometry experiments. Histological modifications were assessed by light and electron microscopes, while degradation of mitochondria was quantified through confocal microscope. Results: Feeding rabbits 2% cholesterol diet for 8 weeks and treatment of cultured cardiomyocytes with 10 mu g/mL cholesterol for 3 h induced excessive autophagic activity via IRE1/JNK pathway. While no change in ER-associated degradation (ERAD) and apoptotic cell death were determined, electron and confocal microscopy analyses in cholesterol supplemented rabbits revealed significant parameters of autophagic cell death, including cytoplasmic autophagosomes, autolysosomes and organelle loss in juxtanuclear area as well as mitochondria engulfment by autophagosome. Either inhibition of ER stress or JNK in cultured cardiomyocytes or alpha-tocopherol supplementation in rabbits could counteract the effects of cholesterol. Conclusion: Our findings underline the essential role of hypercholesterolemia in stimulating IRE1/JNK branch of ER stress response which then leads to autophagic cell death in heart tissue. Results also showed alpha-tocopherol as a promising regulator of autophagic cell death in cardiomyocytes. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Hypercholesterolemia; Endoplasmic reticulum stress; Autophagic cell death; Cardiomyocyte; alpha-Tocopherol; ENDOPLASMIC-RETICULUM STRESS; INDUCED OXIDATIVE STRESS; VITAMIN-E; PROTECTIVE ROLE; QUALITY-CONTROL; ANTIOXIDANTS; MECHANISMS; PROTEASOME; APOPTOSIS; MITOCHONDRIA